Feed System Design of a Parabolic Reflector Antenna for Malaysia Shaped Beam Coverage - Fauzi, N.F.; Yamada, Y.; Ali, M.T.; Abd. Rahman, N.H. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
For Malaysia satellite communication services, MEASAT 3 is now in operation. Based on the satellite footprint, the contour beam shape for Malaysia coverage can be improved by employing multi-beam technology. In order to achieve precise multi-beam positions in a parabolic reflector antenna system, adequate feed horn positions are clarified through focal region ray tracings. In this paper, feed horn positions for practical Malaysia beams are determined based on the focal region data. Next, radiated beams of a parabolic reflector antenna are calculated by using the electromagnetic simulator. Through achievement of excellent beam shapes and positions for Malaysia region, the adequateness of feed horn position designing is ensured.